Influence of distance from lens to sample surface on spectral sensitivity of femtosecond laser-induced breakdown spectroscopy with NaCl water film - Wang, Ying; Gao, Heyan; Hong, Yanji; Zhang, Dan; Chen, Anmin; Jin, Mingxing (Frontiers in Physics, 2022)
Increasing the emission intensity of laser-induced breakdown spectroscopy (LIBS) is an effective way to improve the sensitivity of LIBS technology to elements analysis in liquid samples. In this work, the influence of the distance from lens to sample surface (DFLS) on the spectral emission of femtosecond laser-induced plasma of NaCl water film was studied by measuring Na atomic line. The results showed that the emission intensity of the spectral line presented the phenomenon of double peaks with an increase in the DFLS. The position for the highest spectral intensity was not geometric focal point of focusing lens, but was located in front of the geometric focal point. In addition, we carried out quantitative analysis on Na element with different concentrations, showing a calibration curve of Na element, and calculating limit of detection (LOD) and relative standard deviation (RSD) for different DFLSs. Subsequently, the changes in the LOD and RSD with the DFLS are discussed. With the increase of the DFLS, the LOD and RSD were greatly reduced. At the DFLS of 99.0 mm, the line intensity was highest, and the LOD and RSD were better. Therefore, it can be confirmed that femtosecond LIBS of water film can be optimized by changing the DFLS, the experiment shows great potential in real-time water quality monitoring.